Avaliação da eficácia de atropina e pralidoxima na intoxicação aguda por clorpirifós e desenvolvimento de metodologia analítica para identificação e quantificação de organofosforados e seus antídotos por HPLC-MS/MS - Marques, Graziany Leite Moreira (2016)
Organophosphorus insecticides (OP) are probably the most widely used pesticides in the world. In Brazil, these compounds are considered one of the main responsible for poisoning. Chlorpyrifos (CPF), an OP compound highly used, promotes, similarly to other OP, inhibition of the cholinesterases (ChEs) leading to the accumulation of acetylcholine in the central and peripheral cholinergic synapses. The treatment for OP poisoning involves a combination of muscarinic antagonists, such as atropine (ATR); oximes for reactivating the ChEs, mainly represented by the pralidoxime (2-PAM) and benzodiazepines, generally diazepam, for treatment of occasional seizures. However, the effectiveness of oximes in humans is still doubtful, mainly due to the polarity of these compounds, which leads to poor penetration of these drugs into the central nervous system (CNS). Therefore, this study aims to investigate the efficacy of the antidotes adopted in the OP poisoning, over the clinical signs and on the reactivation of the ChEs inhibition induced by the acute poisoning with CPF, as well as validate analytical method for identifying and quantifying various OPs, ATR and 2-PAM, using high-performance liquid chromatography coupled to mass spectrometry (HPLCMS/MS). Adult male rats (n=280) were divided into 8 groups: saline (SAL), CPF, SAL+ATR, CPF+ATR, SAL+2-PAM, CPF+2-PAM, SAL+ATR+2-PAM and CPF+ATR+2-PAM. The antidotes treatment with ATR (10 mg/kg); 2-PAM (40 mg/kg) or ATR (10mg/kg) +2-PAM (40 mg/kg) was delivered by intraperitoneal injections (i.p.) one hour after the administration of CPF (30 mg/kg, i.p.) or SAL (0.9%, i.p.) and the animals were observed for acute toxicity signs for up to 5 hours. In periods of 15 minutes, 30 minutes, 1 hour, 2 hours, 3 hours, 4 hours and 24 hours after the antidotes treatment administration, the animals were decapitated for collecting blood and brain (except cerebellum) samples for measurements of ChEs activity, as well as for CPF and CPF-oxon analysis by HPLC-MS/MS. The method developed for the OPs and antidotes analysis proved to be efficient and fast, attending the validation criteria stated in the RDC nº 27 of ANVISA (BRASIL, 2012). The analysis demonstrates that the CPF blood concentration significantly decreased over the first 24 hours after administration. The CPF caused inhibition of plasma ChE and treatment with 2-PAM was capable of reversing this inhibition for up to 1 hour after administration. However, when considering the brain AChE the 2-PAM only induced a small reactivation of the enzyme from the second hour of the treatment administration. Although not fully effective, the treatments with ATR, 2-PAM or ATR+2-PAM employed prevented or reverted, at different levels, the typical cholinergic symptoms of the OP poisoning.